2014
DOI: 10.1158/0008-5472.can-14-1482
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived Osteopontin Suppresses Antitumor Immunity by Promoting Extramedullary Myelopoiesis

Abstract: Extramedullary myelopoiesis occurs commonly in tumor-bearing animals and is known to lead to accumulation of peripheral myeloid-derived suppressor cells (MDSC), which play an important role in immune escape. However, the cellular and molecular mechanisms by which tumors induce extramedullary myelopoiesis are poorly understood. In this study, we found that osteopontin expressed by tumor cells enhances extramedullary myelopoiesis in a CD44-dependent manner through the Erk1/2-MAPK pathway. Osteopontin-mediated ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 51 publications
3
30
1
Order By: Relevance
“…In addition, recent studies indicated that OPN also had an immunosuppressive role in tumor milieu. Kim et al reported that tumor-derived OPN could lead to accumulation of peripheral myeloid-derived suppressor cells (MDSC), which were potent immunosuppressive cells [30]. These diverse mechanisms could potentially account for the results that OPN was associated with tumor aggressiveness in this meta-analysis.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, recent studies indicated that OPN also had an immunosuppressive role in tumor milieu. Kim et al reported that tumor-derived OPN could lead to accumulation of peripheral myeloid-derived suppressor cells (MDSC), which were potent immunosuppressive cells [30]. These diverse mechanisms could potentially account for the results that OPN was associated with tumor aggressiveness in this meta-analysis.…”
Section: Discussionmentioning
confidence: 82%
“…We confirmed the trametinib-driven decrease in osteopontin secretion in separate ELISA experiments (Figure 7B). We focused on osteopontin because it has been reported to induce MDSCs expansion (25) and tumor recruitment of macrophages (24). Supporting the relevance of our proteomic analysis, the tumor-driven increase of osteopontin in plasma was abrogated by short-term (3 day) treatment with trametinib in Brpkp110-bearing mice (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, osteopontin has been implicated in the recruitment of macrophages into tumors (23) and its expression is positively correlated with CD204 + M2-like macrophages (24). Osteopontin secreted by tumor cells has also been reported to drive the expansion of MDSCs in the spleens of tumor-bearing mice through activation of the ERK1/2-MAPK pathway in myeloid progenitors (25). …”
Section: Introductionmentioning
confidence: 99%
“…centrifugation step at room temperature, and the cells were subsequently incubated for an additional 18 h (for the B/Mo/αGC preparation this step was skipped). αGC (KRN7000, Enzo Life Science, Japan) was loaded into the prepared B cells and monocytes for NKT activation based on our previous studies20212251.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that an invariant natural killer T (NKT) cell ligand, alpha-galactosylceramide (αGC), loaded on a tumour antigen (tAg)-expressing B cell- and monocyte-based vaccine (B/Mo/tAg/αGC) elicited diverse anti-tumour immune responses202122. In this study, we found that B/Mo/tAg/αGC effectively eradicated otherwise resistant MHC class I-deficient tumour cells by activating NKT cells and inducing tumour antigen-specific cytotoxic T-cell responses.…”
mentioning
confidence: 99%